Meningkatkan Hasil Belajar dan Keterampilan Berfikir Kritis Siswa melalui Pendekatan Inkuiri pada Konsep Ekosistem Kelas VII A SMP Negeri 3 Kusan Hilir - Pusparini, Dini (Universitas Sebelas Maret, 2017)
Based on the results of science learning process in SMP Negeri 3 Kusan Hilir, in the learning process especially KD 7.2 and KD. 7.4 on Ecosystems, learners are always given conceptual learning and teachers are reluctant to invite directly to the environment to learn, learners do not do the learning in groups so that learning is still centered on the teacher. Such learning leads to the lack of creativity and involvement of learners in the learning process that impacts on the classical completeness of only 60%. The purpose of this study is to improve the ability to think critically about what is happening in their environment and to instill environmental ethics in their minds, that the importance of environmental sustainability for the present to the future by using Inquiry approach. This research is Classroom Action Research (PTK). This study was conducted 2 cycles in accordance with the effective learning time of 8 hours lesson. Cycle I as much as 2 meetings and cycle II as much as 2 times meetings. Subjects in this study were students class VII A SMP Negeri 3 Kusan Hilir which amounted to 22 students consisting of 10 women and 12 men. The results showed that by using the Inkuiri approach can improve students' critical thinking skills from classical mastery 13.63% in the first cycle of meeting 1 to 45.50% at the 2nd meeting and 68% in the second cycle of meeting 1 to 95% At the meeting 2. The cognitive learning outcomes of learners have increased from classical completeness 22.72% in the first cycle of meeting 1 to 55% at meetings 2 and 77% in cycle II meeting 1 to 95% at the meeting 2. The implementation process Lessons from the less category in the first cycle of meeting 1 become sufficient category at the 2nd meeting and from the good category in the second cycle of meeting 1 become very good category at the meeting 2. Positive student response to the learning process using Inquiry approach.